Message framing for smoking cessation: the interaction of risk perceptions and gender. - Toll, Benjamin A; Salovey, Peter; O'Malley, Stephanie S; Mazure, Carolyn M; Latimer, Amy; McKee, Sherry A (Nicotine & tobacco research : official journal of the Society for Research on Nicotine and Tobacco, 2008)
Because quitting smoking is clearly linked to preventing health problems such as lung cancer, research on health message framing based on prospect theory suggests that gain-framed messages (i.e., emphasizing the benefits of quitting smoking) would be more persuasive in promoting cessation than loss-framed messages (i.e., emphasizing the costs of continuing to smoke). However, because women tend to anticipate greater perceived risk from quitting smoking than men, this may affect how receptive they are to specific message framing interventions. Data from 249 participants (129 females, 120 males) in a clinical trial of message framing for smoking cessation with bupropion were used to examine how gender differences in perceptions of the risks associated with quitting influence the effects of framed interventions using number of days to smoking relapse as the criterion. Perceived risk of quitting scores were dichotomized using a median split for the entire sample. Women reported a higher perceived risk of cessation than men. Participants who anticipated high risks associated with quitting smoking reported fewer days to relapse. Further, females in the gain-framed condition who reported low perceived risks of cessation had a greater number of days to relapse, as opposed to females in the loss-framed condition. These findings suggest that message framing interventions for smoking cessation should consider the influence of gender and risk perceptions associated with quitting on the effectiveness of framed interventions.
Keywords: Adult; Advertising as Topic; Behavior, Addictive; Bupropion; Dopamine Uptake Inhibitors; Female; Health Behavior; Humans; Male; Middle Aged; Persuasive Communication; Risk Factors; Sex Factors; Smoking; Smoking Cessation; Suggestion; Treatment Outcome